A Wild Fire Detection Balloon Using Thermal Camera - Hashim, Luqman; Shabani, Hikma (Progress in Engineering Application and Technology, 2023)
There have been many cases about forest burning and wildfires. Climate change, rising temperature, drought condition has been the major factor which led to the incident. Major cases such as forest burning in Australia in January,2020 has shown how disastrous a wildfire can be. The problem with existing forest fire detection is most of them are not continuously reading the same area. A good wild fire detection system should be able to continuously monitor every part of the forest at once. This study is to create a forest detection device that has low maintenance cost, safe and can cover a big area. Firefighter are expected to get real time information about any wild fire occurrence. One node from the system made will cover an area of the forest with one thermal camera. There will be several nodes place in the forest that will intercept with each other to cover all area of the forest. Time taken, fire temperature and radius covered are recorded.